2020
DOI: 10.1108/k-05-2020-0268
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of trust in leader in the relations of ethical leadership and distributive justice on internal whistleblowing: a study on Turkish banking sector

Abstract: Purpose The purpose of this paper is to explain the effect of perceived ethical leadership and perceived distributive justice on internal whistleblowing intention through trust in leader as a mediator. Design/methodology/approach Following an empirical design, data were collected from 1,296 employees of Turkish financial institutions, located in Istanbul. To test four hypotheses structural equation modelling was applied. Findings Results reveal that trust in a leader fully mediates the positive effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 116 publications
0
17
0
Order By: Relevance
“…Given that the nurses who participated in this study worked in public hospitals, some may not have reported their real thoughts because of social desirability bias and cultural characteristics. For example, since Turkey is high in collectivism, nurses may see the reporting of these behaviours as external whistleblowing, which are viewed as a threat to organizational unity (Alpkan et al., 2020; Brody et al., 1998). Supporting this notion Earley (1989) emphasized that collectivist cultures, key dynamics of which are cooperation and working with others, are not prone to social loafing.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the nurses who participated in this study worked in public hospitals, some may not have reported their real thoughts because of social desirability bias and cultural characteristics. For example, since Turkey is high in collectivism, nurses may see the reporting of these behaviours as external whistleblowing, which are viewed as a threat to organizational unity (Alpkan et al., 2020; Brody et al., 1998). Supporting this notion Earley (1989) emphasized that collectivist cultures, key dynamics of which are cooperation and working with others, are not prone to social loafing.…”
Section: Discussionmentioning
confidence: 99%
“…Various scholars have also used this scale in their studies. For instance, the studies of Abuzaid [ 128 ] and Alpkan et al [ 129 ] are some evocative examples. Finally, the items of pro-environmental behavior were adapted from Robertson and Barling [ 130 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, Abuzaid [119] used this scale in his study to measure ETL in the banking sector of Jordan. Likewise, Alpkan et al [120] operationalized ETL in their research by using the same scale in the context of the Turkish banking sector…”
Section: Measures and Addressing The Issue Of Social Desirabilitymentioning
confidence: 99%